Malignant peripheral nerve sheeth tumors (MPNST) – case report - Ziółkowska, Ewa; Mross, Mariusz; Biedka, Marta; Makarewicz, Roman (Contemporary Oncology/Współczesna Onkologia, 2007)
Malignant peripheral nerve sheath tumours (MPNST) are a rare entity accounting for 5%-10% f soft-tissue sarcomas. They mostly arise de novo, especially in patients suffering from neurofibromatosis. MPNST mostly arise in the trunk (50%), followed by the extremities (30%) and the head and neck region (20%). Distant metastases are common (40%-80%) and they are most frequently found in the lung and liver. Less common locations are: bone, soft tissue, adrenal glands, brain, ovaries and kidneys. The main treatment is wide surgical excision, which is reported as paramount to local control with adjuvant radiotherapy and brachytherapy.